2018
DOI: 10.1021/jacs.8b08138
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Two-Point Surface Attachment on Enzyme Stability and Activity

Abstract: Immobilization on solid supports provides an effective way to improve enzyme stability and simplify downstream processing for biotechnological applications, which has been widely used in research and in applications. However, surface immobilization may disrupt enzyme structure due to interactions between the enzyme and the supporting substrate, leading to a loss of the enzyme catalytic efficiency and stability. Here, we use a model enzyme, nitroreductase (NfsB), to demonstrate that engineered variants with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
73
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(80 citation statements)
references
References 81 publications
(140 reference statements)
2
73
0
Order By: Relevance
“…disruption of the initial pattern observed inFigure 5bmay be related to the decrease in activity observed experimentally in ref (69)…”
supporting
confidence: 62%
See 2 more Smart Citations
“…disruption of the initial pattern observed inFigure 5bmay be related to the decrease in activity observed experimentally in ref (69)…”
supporting
confidence: 62%
“…Nitroreductase (NfsB) is a FMN-dependent homodimeric enzyme which catalyzes the reduction of a wide range of substrates containing nitro-groups. It is well characterized both structurally and functionally, and often serves as a model system to study how surface interactions will affect enzyme stability and activity [66][67][68][69] . Recently, Zou et al…”
Section: Adsorbed Nitroreductasementioning
confidence: 99%
See 1 more Smart Citation
“…Similar orientation effects are well known for enzyme and the vastly explored RGD peptide immobilization [ 65 , 66 ]. Other factors such as the specific residue anchoring point (and number of them) affect activity as well, including peptide density [ 67 , 68 ]. Previous work has shown that peptide density, which we did not control here, can affect cell adhesion, differentiation, and focal adhesion formation [ 48 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, the molecular mechanisms taking place upon enzyme immobilization are not well understood. While most experiments on immobilized proteins, either via a covalent [28][29] or non-covalent [30][31][32] strategy, report a decrease in their catalytic activity, sometimes enzyme immobilization can also result in an important increase of the catalytic performance. 33 Numerous enzyme immobilization strategies have been developed, that involve simple adsorption via electrostatic or van der Waals interactions, the use of porous materials, crosslinking, or multipoint-covalent attachment, [33][34][35] and many experimental approaches are now available to investigate protein immobilization on solid surfaces, including atomic force microscopy, mass spectrometry and spectroscopic methods.…”
Section: Introductionmentioning
confidence: 99%